Problem-Based Learning Model: An Effort To Improve Student Learning Outcomes In Class XI SMA Negeri 2 Tondano - Rafyansa Papunas; Orbanus Naharia; Mariana Rengkuan (International Forum of Researchers and Lecturers, 2023)
The objective of this study is to assess the enhancement in student learning outcomes subsequent to the implementation of the Problem-Based Learning instructional approach in the eleventh grade of SMA Negeri 2 Tondano, located in the Sangihe Islands district, during the academic year 2022/2023. The present study is an instance of classroom action research (PTK) employing an action cycle that encompasses action preparation, implementation, observation, and reflection. The participants of this study consisted of 18 students from class XI MIPA3 at SMA N 2 Tondano. The data gathering methods encompass the assessment of student learning outcomes through the utilisation of test result data conducted at the conclusion of each instructional cycle. The data analysis was conducted using a quantitative descriptive approach. The findings of the study indicated that the implementation of questionnaires in cycle I resulted in a significant improvement in students' learning outcomes. The sample size for this phase of the research consisted of 18 participants. The completion rate of students' learning outcomes exhibited an upward trend, rising from 79.94% in cycle I to 86.27% in cycle II. The observed rise in student learning scores over each cycle suggests that the utilisation of the Problem-Based Learning model has the potential to enhance the learning outcomes of students in class XI MIPA3 SMA N 2 Tondano.